Comparative analysis of mobile applications for IT project management - Wlaszczyk, Ewelina; Miłosz, Elżbieta (Journal of Computer Sciences Institute, 2018)
The article presents the results of a comparative analysis of selected applications for Android mobile system used to manage IT projects. The research was carried out using multicriteria analysis on the functionality, intuitiveness and appearance of the interface and the available data integration of the application.